Biostimulants induce positive changes in the radish morpho-physiology and yield - Raza, Qurat-Ul-Ain; Bashir, Muhammad Amjad; Rehim, Abdur; Ejaz, Rafia; Raza, Hafiz Muhammad Ali; Shahzad, Umbreen; Ahmed, Faraz; Geng, Yucong (Frontiers in Plant Science, 2022)
An ever-increasing population has issued an open challenge to the agricultural sector to provide enough food in a sustainable manner. The upsurge in chemical fertilizers to enhance food production had resulted in environmental problems. The objective of the current study is to assess the utilization of biostimulants for sustainable agricultural production as an alternative to chemical fertilization. For this purpose, two pot experiments were conducted to examine the response of radish against individual and combined applications of biostimulants. In the first experiment, the effects of chemical fertilizer (CK), glycine (G), lysine (L), aspartic acid (A), and vitamin B complex (V) were studied. The results demonstrated that V significantly improved the transpiration rate (81.79%), stomatal conductance (179.17%), fresh weight (478.31%), and moisture content (2.50%). In the second experiment, tested treatments included chemical fertilizer (CK), Isabion® (I), glycine + lysine + aspartic acid (GLA), moringa leaf extract + GLA (M1), 25% NPK + M1 (M2). The doses of biostimulants were 5g L−1 glycine, 1g L−1 lysine, 2g L−1 aspartic acid, and 10 ml L−1 moringa leaf extract. The photosynthetic rate improved significantly with GLA (327.01%), M1 (219.60%), and M2 (22.16%), while the transpiration rate was enhanced with GLA (53.14%) and M2 (17.86%) compared to the Ck. In addition, M1 increased the stomatal conductance (54.84%), internal CO2 concentration (0.83%), plant fresh weight (201.81%), and dry weight (101.46%) as compared to CK. This study concludes that biostimulants can effectively contribute to the sustainable cultivation of radish with better growth and yield.